Effects of temperature on the cuticular transpiration barrier of two desert plants with water-spender and water-saver strategies. (30th January 2019) - Bueno, Amauri; Alfarhan, Ahmed; Arand, Katja; Burghardt, Markus; Deininger, Ann-Christin; Hedrich, Rainer; Leide, Jana; Seufert, Pascal; Staiger, Simona; Riederer, Markus
Highlight: The efficacy of the cuticular transpiration barrier and its resistance to elevated temperatures are significantly higher in a typical water-saver than in a water-spender plant growing in hot desert. Abstract: Water-saver and water-spender strategies are successful adaptations allowing plants to cope with the limitations of hot desert habitats. We investigated whether the efficacy of the cuticular transpiration barrier and its susceptibility to high temperatures are ecophysiological traits differentially developed in the water-spender Citrullus colocynthis and the water-saver Phoenix dactylifera . Minimum leaf conductance ( g min ) at 25 °C was six times lower in P. dactylifera (1.1×10 –5 m s –1 ) than in C. colocynthis (6.9×10 –5 m s –1 ). Additionally, g min in the range 25–50 °C did not change in P. dactylifera but increased by a factor of 3.2 in C. colocynthis . Arrhenius formalism applied to the C. colocynthis g min led to a biphasic graph with a steep increase at temperatures ≥35 °C, whereas for P. dactylifera the graph was linear over all temperatures. Leaf cuticular wax coverage amounted to 4.2±0.4 µg cm –2 for C. colocynthis and 29.4±4.2 µg cm –2 for P. dactylifera . In both species, waxes were mainly composed of very-long-chain aliphatics. Midpoints of the wax melting ranges of P. dactylifera and C. colocynthis were 80 °C and 73 °C, respectively. We conclude that in P. dactylifera a particular wax and cutin chemistry prevents the rise of g min at elevated temperatures.